A footwear marks database in Western Switzerland: A forensic intelligence success - Pasquier, Julien (Forensic science international, 2023)
Footwear marks database has been the subject of numerous research projects over the past decades with a strong focus on the automation of the process of retrieving candidates for comparison. However, to date, there is still no tool able to perform a fully automate treatment of unknown crime scene marks. Making the assumption that a fully automated tool would not be available before a long time and not necessarily required, a project has emerged in Western Switzerland with the aim to commonly exploit footwear marks across several states. As this type of evidence is mainly collected in the context of volume crime, the exploitation of the footwear marks is mainly focused on the detection of links between cases in order to create forensic intelligence. Nevertheless, the search for associations between unknown marks and seized shoes is also carried out. This project resulted in a database developed in-house and now in operation. Through this tool, several forensic services are able to share their footwear marks, compare them and detect series. The links detected through this database are also shared with criminal analysis and intelligence systems. This project does not exploit any particular technological advance but have led to an operational database. This paper will highlight some of the factors that have led to the development and implementation of a successful footwear marks database connecting several police services. •SID is a footwear marks database linking four different forensic services.•36.5% of inserted cases are linked to one or more other cases through footwear.•Technology is not a key factor for success of a footwear mark database.•Contextualisation of the trace is one the success factors.